Social Rehabilitation of Prisoners in Ukrainian Prisons by Kharkov Region - Klochko, Marianna (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
This article addresses the issue of “time discounting” and its relationship with deviant behavior, whereas higher levels of delinquency are affected by a desire for immediate gratification, or high level of discounting of behavioral consequences. Ideally rehabilitation process should help prisoners to extend their time horizons and start valuing the future, which will help to prevent future deviant behavior. Data analysis showed that in Ukraine the ability to defer gratification is more likely to be exhibited by females, older people, those who receive letters by mail, and those who are single. Contradictory to the initial expectations time discounting is actually increased with factors such as spending time in mandatory rehabilitation programs, spending time in prison, and being in prison repeatedly, which allows us to start questioning the effectiveness of prison rehabilitation.